NATIONAL TRADITIONS AND CUSTOMS OF THE KYRGYZ PEOPLE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article analyzes the national traditions and customs, which are considered an important element of the Ferghana Valley Kyrgyz culture, in particular, traditions related to mourning and mourning ceremonies, national handicrafts, as a factor of preserving national identity